2012
DOI: 10.1515/jpem-2012-0054
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive measurement of adrenal response after standardized exercise tests in prepubertal children

Abstract: Objective:To determine the feasibility of non-invasive evaluation of adrenal response in healthy prepubertal children by standardized exercise tests. Methods: On separate occasions, healthy prepubertal children performed a submaximal cycling test, a maximal cycling test, and a 20-m shuttle-run test. Salivary cortisol levels were determined before exercise, and 1 and 15 min after exercise. Results: Immediately after cessation of the cycling and shuttle-run tests, salivary cortisol levels remained unchanged or d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 19 publications
1
4
0
4
Order By: Relevance
“…One study (Budde et al, 2010b ) with prepubescent children found no cortisol elevation after acute physical activity and another study (Benitez-Sillero et al, 2009 ) found an elevation only in physically fit children. A third study (Heijsman et al, 2012 ) reported no elevation when cortisol was assessed immediately after acute physical activity, but did so when it was assessed again 15 min later. This finding is in line with results showing that the peak of cortisol concentration occurs with a latency of 20–30 min following physical activity (Kirschbaum and Hellhammer, 1994 ; Daly et al, 2005 ).…”
Section: Introductionmentioning
confidence: 98%
“…One study (Budde et al, 2010b ) with prepubescent children found no cortisol elevation after acute physical activity and another study (Benitez-Sillero et al, 2009 ) found an elevation only in physically fit children. A third study (Heijsman et al, 2012 ) reported no elevation when cortisol was assessed immediately after acute physical activity, but did so when it was assessed again 15 min later. This finding is in line with results showing that the peak of cortisol concentration occurs with a latency of 20–30 min following physical activity (Kirschbaum and Hellhammer, 1994 ; Daly et al, 2005 ).…”
Section: Introductionmentioning
confidence: 98%
“…We recruited 10 healthy children and 10 children with asthma for this pilot study. For practical reasons, children who had participated in a previous trial were invited to participate in the present study . Briefly, children with asthma were eligible if they were six to12 years of age, prepubertal according to Tanner stage, were using maintenance inhaled corticosteroids (with or without concomitant use of intranasal steroids) for a minimum of 3 months, and their asthma was well controlled.…”
Section: Introductionmentioning
confidence: 99%
“…Parents were instructed to record the sampling time on the Salivettes ® . The saliva samples were centrifuged at 1000 g for 2 min at room temperature, and cortisol was measured using a liquid chromatography tandem mass spectrometry (LC‐MS/MS) assay as described previously .…”
Section: Introductionmentioning
confidence: 99%
“…Es evidente que, aun hallando disparidad en los resultados sobre niveles de cortisol en la práctica físico-deportiva, el estudio de esta hormona sigue siendo interesante porque refleja la influencia física y psicológica, dualidad que es necesaria analizar. En esta línea, diferentes investigaciones (Bouget, Rouveix , Michaux, Pequignot y Filaire, 2006;Doan, Newton, Kraemer, Kwon y Scheet, 2007;Minetto et al, 2007;Crewther, Cronin, Keogh y Cook, 2008;Beaven, Gill y Cook, 2008; Moreira, Arsati, de Oliveira, da Silva y de Arau´ jo, 2009, Lusa Cadore et , 2009;Heijsman et al, 2012) llevadas a cabo en diferentes edades y prácticas físico-deportivas, señalan que la relación entre los niveles de cortisol salival y el estrés psicofisiológico, aportan una herramienta indicadora de auto-reporte psicológico y cambios de los niveles de ansiedad relacionados con los éxitos en la práctica del ejercicio físico. al respecto, Hanton, Thomas y Maynard (2004) indican que el mismo nivel de ansiedad puede ser autopercibido por deportistas bien como facilitadores o como debilitadores respecto a su rendimiento deportivo.…”
Section: Mots Clésunclassified